THE MODERATING ROLE OF PSYCHOLOGICAL EMPOWERMENT ON THE RELATIONSHIP BETWEEN BENEVOLENT LEADERSHIP AND WELL-BEING IN THE CONTEXT OF EMPLOYEES WITH DISABILITIES - Gugup Kismono; Dwita Safira Pranabella (Journal of Leadership in Organizations, 2021)
Main Objectives: This study aims to evaluate the moderating role of psychological empowerment on the relationship between benevolent leadership and employees’ well-being.Novelty: Since research involving disabled employees is rare, this study adds to the current body of knowledge by confirming the links between benevolent leadership, job satisfaction, and perceived discrimination. It also aims to find out how psychological empowerment influences the relationship between benevolent leadership and job satisfaction, as well as the association between benevolent leadership and perceived discrimination. Research methods: This research involves 85 respondents. They are employees with various disabilities working in different organizations. Moderated regression analysis is employed to analyze the data. Finding/Results: This study found that benevolent leadership significantly affect employees’ well-being: job satisfaction, and perceived discrimination. In addition, as expected, psychological empowerment strengthens the positive impact of benevolent leadership on job satisfaction. On the contrary, psychological empowerment weakens the negative impact of benevolent leadership on perceived discrimination. Conclusion: Based on the conservation of resources theory, resources provided by the organization, in this case is benevolent leadership, perceived by employees with disabilities as a recovery of the loss of resources (disabilities). Recruiting benevolent leaders or developing existing leaders to be more benevolence is important to improve disabilities employees’ well-being.